Development of functional noodles by encapsulating mango peel powder as a source of bioactive compounds - Md Raihan Kabir; S.M. Kamrul Hasan; Md Rakibul Islam; Maruf Ahmed (Heliyon, 2024)
Antioxidant compounds such as phenolics and carotenoids scavenge reactive oxygen species and protect against degenerative diseases such as cancer and cardiovascular disease when used as food additives or supplements. Mango peel is a by-product of mango which is a good source of bioactive substances such as phytochemicals, antioxidants, and dietary fibers. Unfortunately, the study on mango peel as a potential food additive is very limited. Accordingly, the present study aimed to develop functional noodles through extrusion technology with the encapsulation of mango peel powder as a natural source of bioactive compounds. First, mango peel powder (MPP) was prepared and incorporated during the mixing of ingredients before noodles formation at three different levels (2.5, 5 and 7.5 %). Afterward, the noodles were studied to determine how the encapsulated MPP affects the proximate composition, physicochemical characteristics, polyphenols, carotenoids, anthocyanin, antioxidant and antidiabetic activity, and sensory characteristics. The noodles exhibited a dose-dependent relationship in the content of bioactive components and functional activities with the encapsulation of MPP levels. A significantly (p 0.05) higher value was noticed in 7.5 % of MPP-encapsulated noodles than in any level of MPP encapsulation in noodles. The fiber and protein contents in the MPP-encapsulated noodles were increased by about 0–1.22 % and 0–3.16 %, respectively. However, noodles’ color index and water absorption index were decreased with the level of MPP encapsulation. The cooking loss of noodles increased from 4.64 to 5.17, 6.49, and 7.32 %, whereas the cooked weight decreased from 35.11 to 34.40, 33.65, and 33.23 % with 2.5, 5.0, and 7.5 % of MPP encapsulation, respectively. However, MPP was stable during storage of noodles exhibiting higher phenolic content and antioxidant activity than control samples. The sensory evaluation showed that MPP-encapsulated noodles at levels 2.5 and 5 % had approximately similar overall acceptability values with the control sample. As a result of the findings, it appears that adding MPP up to 5 % to noodles improves their nutritional quality without changing their cooking, structural, or sensory aspects. Therefore, mango peel powder can be a potential cheap source for the development of functional noodles and food ingredients.